A novel clinical prediction scoring system of high-altitude pulmonary hypertension - Zeng, Yanxi; Zhakeer, Gulinigeer; Li, Bingyu; Yu, Qing; Niu, Mingyuan; Maimaitiaili, Nuerbiyemu; Mi, Ma; Deji, Zhuoga; Zhuang, Jianhui; Peng, Wenhui (Frontiers in Cardiovascular Medicine, 2024)
Background: High-altitude pulmonary hypertension (HAPH) is a common disease in regions of high altitude where performing right heart catheterization (RHC) is challenging. The development of a diagnostic scoring system is crucial for effective disease screening.Methods: A total of 148 individuals were included in a retrospective analysis, and an additional 42 residents were prospectively enrolled. We conducted a multivariable analysis to identify independent predictors of HAPH. Subsequently, we devised a prediction score based on the retrospective training set to anticipate the occurrence and severity of HAPH. This scoring system was further subjected to validation in the prospective cohort, where all participants underwent RHC.Results: This scoring system, referred to as the GENTH score model (Glycated hemoglobin (OR=4.5), Echocardiography sign (OR=9.1), New York Heart Association-functional class (OR=12.5), Total bilirubin (OR=3.3), and Hematocrit (OR=3.6)), incorporated five independent risk factors and demonstrated strong predictive accuracy. In the training set, the area under the curve (AUC) for predicting the occurrence and severity of HAPH was 0.851 and 0.832, respectively, while in the validation set, it was 0.841 and 0.893. In the validation set, the GENTH score model cutoff values of ≤ 18 or >18 points were established for excluding or confirming HAPH, and the threshold of > 30 points indicated severe HAPH.The GENTH score model, combining both laboratory and echocardiography indicators, represents an effective tool for distinguishing potential HAPH patients and identifying those with severe HAPH. This scoring system enhances the clinical screening of HAPH diseases and offers valuable insights into disease diagnosis and management.